French-Language Books in a Minority Setting: A Report from Rural Saskatchewan - Russo, Richard (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2019)
Public libraries are potential institutional spaces for maintaining the vitality of official language minority communities (OLMCs). This study establishes baseline data on the number and characteristics of French-language books in Saskatchewan’s minority Francophone communities, with a detailed look at six rural communities with the greatest proportion of Francophones. Data collection involved site visits to branch libraries and community centers during which more than 5,000 online catalogue library records of books intended for adult readers were reviewed. The results of the study show that a spatial mismatch exists between Francophone residents and French-language books held in Saskatchewan’s public libraries. It is recommended that OLMCs collaboratively revisit library collection policies, so that book acquisitions can better support Francophone identity and culture through lifelong learning and leisure.